Structural features of low-stable phase states of aqueous solutions at ultrahigh dilution - Potekaev, A. I.; Obukhov, V. V.; Odintsov, S. D. (Russian physics journal, 2025)
A physical concept of thermodynamic structural-phase states of a physical system is proposed in application to ultrahigh diluted aqueous solutions low-stable to external impacts. The physical analogy between the states of these solutions and the condensed physical systems helps to understand physics of various effects observed in ultrahigh diluted aqueous solutions. In particular, this approach allows the role of shaking of the chemical solutions in the Epstein effect to be evaluated by mechanochemical methods. An analysis of the thermodynamic and structural-phase low-stable states of the physical system makes it possible to propose a possible mechanism for the system transition to a new phase state under a low-stable external impact on the example of an ordering alloy system. In this case, the small external impact (for example, shaking) can lead to significant phase changes of the system state in which the structural units are close thermodynamically, but can differ significantly in symmetry. It is discussed how the effect of the state of the suitable symmetric liquid solution of a substance under a small external impact (for example, in the form of shaking) can be experimentally realized.